PENGEMBANGAN VIDEO ANIMASI INFORMASI KARIR UNTUK PERENCANAAN KARIR DI SEKOLAH MENENGAH PERTAMA - Muharandri, Citra; Astuti, Indri; Putri, Amallia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
Developing animated videos is the aim of this research. The ADDIE development model is used in conjunction with Research and Development (RD) methods. There are several stages of research using the ADDIE development model: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. Six expert validation participants and 69 class IX students of SMP Negeri 18 Pontianak participated in this research. Data collection includes questionnaires and indirect interviews. Data from questionnaires are tested using descriptive analysis. The animated video material was validated by two material experts (average score of 3.5), two media experts (average score of 4.06), and two design experts (average score of 4.5) in the "very valid" category. Next, we tested the empirical test results using an individual test procedure consisting of 3 people (average score 4.31 in the "very happy" category), a small group of 6 people (average score 4.51 in the "very happy" category), and field trials involving 30 people in class IX E of SMPN 18 Pontianak (average score 4.46 in the range 1"“5). Students were "very happy" with using animated video media. With a p value 0.05 or 0.001 0.05 The pretest and posttest effectiveness tests, which involved thirty students, revealed a significant difference.. The animated video material was assessed using an effect size test which obtained a result of 1.45 in the "Strong Effect" category. Junior high school career planning resources, such as animated career information videos, can be used to provide information, guidance, and counseling services.